DRUG INTERACTIONS AND CONTRAINDICATIONS ANESTHESIA DRUGS IN PSYCHIATRIC PATIENTS - Wardani, Henry Nur Kusuma; Pramono, Wisnu Budi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Psychotropic drugs are used in the treatment of psychiatric and non-psychiatric conditions. Many patients taking psychotropic medications may present for procedures that require anesthesia. Psychotropic drugs can have dangerous interactions with drugs commonly used in anesthesia, some of which can be life-threatening. In this review, we describe current anesthetic considerations for patients undergoing psychotropic drug therapy, including antidepressants, antipsychotics, mood stabilizers, anxiolytics, and stimulants. The pharmacology, side effects, and potential drug interactions of commonly prescribed psychotropic drug therapy with anesthetic agents are described. Next, we highlight current recommendations regarding discontinuation and continuation of these medications during the perioperative period.